2005
DOI: 10.1177/107602960501100206
|View full text |Cite
|
Sign up to set email alerts
|

A Protocol for the Use of Enoxaparin During Pregnancy: Results from 85 Pregnancies Including 13 Multiple Gestation Pregnancies

Abstract: Many practitioners consider low-molecular-weight heparin (LMWH) an alternative to unfractionated heparin, although there are limited safety data regarding maternal and fetal outcomes in patients using an LMWH during pregnancy. A retrospective chart review was performed on 72 patients with thrombophilia exposed to the LMWH, enoxaparin, during pregnancy. Eighty-five pregnancies resulted in 93 of 99 potential live births. Eleven of 12 twin pregnancies and one triplet pregnancy were successful. One preterm live bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Still, the frequency of antifactor Xa monitoring in pregnancy has not been well described, and there are no established recommendations. Although limited reports show inconsistent results on the necessity of antifactor Xa monitoring, [22][23][24] our results suggest that if the desired targets 9 are to be achieved, antifactor Xa monitoring may be desirable. In our practice, we found that monthly antifactor Xa levels were reasonable to assess the need for dosage adjustments; additional information in the future may obviate the need for such frequent testing.…”
Section: Discussionmentioning
confidence: 69%
“…Still, the frequency of antifactor Xa monitoring in pregnancy has not been well described, and there are no established recommendations. Although limited reports show inconsistent results on the necessity of antifactor Xa monitoring, [22][23][24] our results suggest that if the desired targets 9 are to be achieved, antifactor Xa monitoring may be desirable. In our practice, we found that monthly antifactor Xa levels were reasonable to assess the need for dosage adjustments; additional information in the future may obviate the need for such frequent testing.…”
Section: Discussionmentioning
confidence: 69%
“…Following successful use of unfractionated heparin in pregnant women during the 1970's and 1980's [Hirsh et al, 1970;Bonnar, 1976;Spearing et al, 1978;Anon (c), 1979;de Swiet et al, 1980;Bonnar, 1981;Chen et al, 1984;Letsky and de Swiet, 1984], as LMWH therapy gained acceptance in antenatal practice through the 1990's, a number of groups began publishing research or information on the pharmacokinetics and use of different LMWH during pregnancy [Priollet et al, 1986;Melissari et al, 1992;Gillis et al, 1992;Sturridge et al, 1994;Hunt et al, 1997;Nelson-Piercy et al, 1997;Blomback et al, 1998;Casele et al, 1999;Brennard et al, 1999;Bremme et al, 2000;Ellison et al, 2000;Crowther et al, 2000;Leqercq et al, 2001;Rodie et al, 2002;Hunt et al, 2003;Jacobsen et al, 2003;Sephton et al, 2003;Norris et al, 2004;Smith et al, 2004;Ensom et al, 2004;Huxtable et al, 2005;Fox et al, 2008;Lebaudy et al, 2008;Ni Ainle et al, 2008;Simpson et al, 2009;Friedrich et al, 2010] (see table 1.10 for a summary of each study). Case report of a patient with a massive ileo-femerol DVT managed with once daily adjusted dose enoxaparin (60-80mg daily) from week 13 of her pregnancy.…”
Section: Pharmacokinetic Studies Of Lmwh During Pregnancymentioning
confidence: 99%
“…10 The evidence for increasing the total daily dose or dosing frequency during pregnancy is based on small, historical, observational studies. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Prescribing a twice-daily dosing regimen of LMWH has significant implications for women with respect to injection burden, particularly if the VTE event occurs early during pregnancy.…”
mentioning
confidence: 99%